Transmisi Model Matematika dalam Berbagai Profesi Kepada Guru Matematika SMA di Sumatera Barat - Susila Bahri; Syafrizal Sy; Ahmad Iqbal Baqi; Riri Lestari; Radhiatul Husna (Universitas Pahlawan Tuanku Tambusai, 2021)
The knowledge and insight of teachers about the use of mathematical material taught to their students at school are minimal. Therefore, it is necessary to transmit the application of mathematical models to each mathematical material discussed in school learning. Transmission through this community service webinar presents several applicable cases or problems directly practiced by various professions such as police, doctors, company managers, area planner, programmers, and demographics. Indirectly, this transmission also aims to make students aware of the importance of mathematics in the world of work (profession) which is their goal in the future. From the results of direct interviews with high school mathematics teachers at the webinar, the service team can conclude that this webinar is beneficial in increasing their knowledge and insight so that this service can be sustainable in the future.